Critical ranges of leaf primary macronutrients levels for irrigated coffee farming the second year after planting - Villela, Gabriel Mendes; Guimarães, Rubens José; Pinto, Clayton Grillo; Scalco, Myriane Stella; Sales Junior, José Carlos; Camilo, Willian Ribeiro; Alves, Gesiel (Coffee Science - ISSN 1984-3909, 2015)
Aimed to establish bands and, or critical levels of foliar concentrations and optimal level of fertilization with nitrogen, phosphorus and potassium to fertirrigated coffee in formation. The experiment was carried out in the field in Setor de Cafeicultura da Universidade Federal de Lavras - MG, March 2010 to July 2013. The experimental design was a randomized block design with six treatments and four replicates. Nutrient levels were 10 % , 40 % , 70 % , 100 %, 130 % and 160 % compared to standard fertilization. In the first cycle of fertirrigation, fertilization was the standard for rainfed crops in training. Chemical analysis was performed in six sheets of times of two months, starting from 13/01/2012. In July 2013 we evaluated the productivity of coffee (L plant - 1) in the second crop, with influences of fertilizer levels. The best level of fertilization with N, P and K is 122.61% compared to standard fertilizer for crops in non-irrigated training. Settled bands and critical levels of foliar N, P and K for crops irrigated coffee in the second year post- planting fertilizer.